2017
DOI: 10.1111/papt.12145
|View full text |Cite
|
Sign up to set email alerts
|

EMDR as a treatment for long‐term depression: A feasibility study

Abstract: ObjectiveCurrent treatments for long‐term depression – medication and psychotherapy – are effective for some but not all clients. New approaches need to be developed to complement the ones already available. This study was designed to test the feasibility of using an effective post‐traumatic stress disorder treatment for people with long‐term depression.DesignA single‐case experimental design with replications was undertaken as a feasibility study of eye movement desensitization and reprocessing (EMDR) in trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…More recently, other studies have reported evidence of EMDR efficacy in patients with depression ( Hofmann et al, 2014 ; Behnammoghadam et al, 2015 ; Hase et al, 2015 ; Mauna Gauhar, 2016 ), while a specific EMDR therapy protocol for the treatment of depressive disorders has been published ( Hofmann et al, 2016 ). Moreover, a recently published study has shown the feasibility of using EMDR treatment in patients with recurrent and/or long-term depression ( Wood et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, other studies have reported evidence of EMDR efficacy in patients with depression ( Hofmann et al, 2014 ; Behnammoghadam et al, 2015 ; Hase et al, 2015 ; Mauna Gauhar, 2016 ), while a specific EMDR therapy protocol for the treatment of depressive disorders has been published ( Hofmann et al, 2016 ). Moreover, a recently published study has shown the feasibility of using EMDR treatment in patients with recurrent and/or long-term depression ( Wood et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CBT + EMDR group showed more complete remissions and a greater reduction in Beck Depression Inventory scores than the CBT-only group (11). The retrieved researches suggest EMDR as a useful supplementary therapy not only in the treatment of MDD with and without co-concurrent trauma history but also in the case of recurrent, long-term symptomatology and treatment-resistant (TR) depression (10,12). Overall, the studies that applied EMDR in MDD showed a reasonable level of evidence ranging from 2 to 5 on the Sackett Scale.…”
Section: Potential Role Of Eye Movement Desensitization and Reprocessing In Mdd Treatment And Its Mechanismmentioning
confidence: 99%
“…However, EMDR has continued to demonstrate effectiveness in a number of other conditions involving adverse life events and stress-mediated symptoms (Shapiro, 2014). Conditions of particular relevance to pPCS include depression (Wood et al, 2018), anxiety (Bandelow et al, 2015), panic disorder (Horst et al, 2017), migraine headaches (Marcus, 2008), functional neurological disorder (Cope et al, 2018), sleep disorder (Raboni et al, 2014), and medically unexplained symptoms and somatoform disorder (Van Rood & De Roos, 2009). One paper demonstrated that short EMDR intervention is feasible and potentially effective in the context of the post-concussion "like" symptoms in the emergency room (Gil-Jardiné et al, 2018).…”
Section: Making a Case For Emdrmentioning
confidence: 99%